The Influence of Locus of Control, Work Environment, and Organizational Support on Performance Through Dynamic Capability as An Intervening Variable in Employees of CV. Berkah Abadi Plywood Kendal - Listya Rini, Indah; Violinda, Qristin; Meiriyanti, Rita (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: This study aims to determine empirically the effect of locus of control, work environment, and organizational support on performance through dynamic capability as an intervening variable in employees of CV. Berkah Abadi Plywood Kendal. Design/Methode/Approach: This research is a type of quantitative research that uses primary data in the form of company annual reports. The population in this study was 130 employees of CV. Berkah Abadi Plywood Kendal with all members of the population used as samples using saturated sampling techniques. Techniques used in data collection by distributing questionnaires as data collection instruments. The data analysis technique used in this study is PLS-SEM (Partial Least Square- Structural Equation Modeling) with data processing using Smart PLS 4.0 tools. Research Finding: Based on the results of data analysis, the research findings are (1) locus of control has a positive effect on employee performance (2) work environment has no effect on employee performance, (3) organizational support has a positive effect on employee performance, (4) locus of control has a positive effect on dynamic capability, (5) work environment has no effect on dynamic capability, (6) organizational support has a positive effect on dynamic capability, (7) dynamic capability has a positive effect on employee performance, (8) locus of control has a positive effect on employee performance, (9) work environment has no effect on employee performance, (10) organizational support has a positive effect on employee performance mediated by dynamic capability.